Phytochemical Screening and Oral Acute Toxicity Study of Aqueous Leaf Extract of Crinum giganteum (Gadalli) in Wister Rats - FB, Elizabeth; E.N, Obikili; A. E, Esom; G.E, Anyanwu (Journal of Phytology, 2016)
Background: Different parts of plants possess variable phytochemical compounds and LD50. Crinum giganteum (Gadalli) is one of the plants most commonly consumed in parts of Africa for its various medicinal values. Despite this popularity, the phytochemical screening and the toxicity of the leaf extracts were yet to be evaluated. This study was designed to identify the bioactive agents and estimate the LD50 for the aqueous leaf extract of gadalli. Method: Phytochemical screening was done using standard methods. Each bioactive agent and the LD50 were estimated by Arithmetic methods of Karber. Results: Phytochemical analysis revealed high presence of alkaloids, saponins, and slight presence of glycosides while the oral LD50 was found to be 200 mg/kg. Conclusion: The major active ingredients of aqueous leaf extract of gadalli are alkaloids and saponins. It is observed to be unsafe at 200mg/kg and above. Keywords: Phytochemicals, Crinum Giganteum, LD50, Alkaloids, Saponins, Glycosides